Selection for niche differentiation in plant communities increases biodiversity effects - Zuppinger-Dingley, Debra; Schmid, Bernhard; Petermann, Jana S.; Yadav, Varuna; De Deyn, Gerlinde B.; Flynn, Dan F. B. (Nature (London), 2014)
Here, new ecological communities are established using plants from mixed-species communities or monocultures; ecosystem functioning and morphological trait diversity are shown to be greater in plants from mixed-species communities, suggesting that biodiversity effects in natural communities strengthen over time. Plants that grow better together More diverse plant communities are often more stable and productive, an effect which tends to increase through time. In this paper, Debra Zuppinger-Dingley et al . investigate the role of evolution in this ecological phenomenon. They assemble new ecological communities using plants — grasses, herbs and legumes — with different recent evolutionary histories, grown in either mixed-species communities or monocultures. Ecosystem functioning and morphological trait diversity were greater in communities of mixture-grown than monoculture-grown plants, suggesting that biodiversity effects in natural communities strengthen as populations adapt to their biotic environment. The finding that small-scale evolution is important to ecological relationships brings together these different perspectives on species coexistence in natural communities. In experimental plant communities, relationships between biodiversity and ecosystem functioning have been found to strengthen over time 1 , 2 , a fact often attributed to increased resource complementarity between species in mixtures 3 and negative plant–soil feedbacks in monocultures 4 . Here we show that selection for niche differentiation between species can drive this increasing biodiversity effect. Growing 12 grassland species in test monocultures and mixtures, we found character displacement between species and increased biodiversity effects when plants had been selected over 8 years in species mixtures rather than in monocultures. When grown in mixtures, relative differences in height and specific leaf area between plant species selected in mixtures (mixture types) were greater than between species selected in monocultures (monoculture types). Furthermore, net biodiversity and complementarity effects 1 , 2 were greater in mixtures of mixture types than in mixtures of monoculture types. Our study demonstrates a novel mechanism for the increase in biodiversity effects: selection for increased niche differentiation through character displacement. Selection in diverse mixtures may therefore increase species coexistence and ecosystem functioning in natural communities and may also allow increased mixture yields in agriculture or forestry. However, loss of biodiversity and prolonged selection of crops in monoculture may compromise this potential for selection in the longer term.